Career Decision Regrets in Faculty of Sport Sciences - Tunckol, H. Mehmet; Uzun, Sena (European Scientific Journal, ESJ, 2024)
University education as an important choice shapes the professional career. Career in sport is difficult than the other professional areas. Because the professional career process in sport is different from the classical occupational choices. Sometimes individuals feel career regret in difficult experiences. Then the negative feelings become a depression, loss of self-confidence etc. So, the purpose of this study was to determine the career decision regrets of students in faculty of sport sciences. The most commonly technique in descriptive research models, the survey method is used in the study. The study group consisted of 400 students from the four different departments in Bartın University, Faculty of Sport Sciences. In the study, individual information form which had developed by the researchers and ‘Career Decision Regret Scale’ was used. Descriptive statistics, t-test for independent groups and one-way Anova tests were used as statistical methods to analyze the data. As a result, it was determined that the students who are studying at the Department of Sports Sciences in Bartın University had a little regret of career decisions and the scale scores of the students differed significantly according to their age, departments, grade, place of birth, academic average, residence place, part time working, fathers’ working statute and educational level. The fact that the study group consists of only one university is seen as a limitation. Therefore, for future studies it may be suggested to increase the number of participants by joining the different universities’ students in the Departments of Sports Sciences.